28th Aerodynamic Measurement Technology, Ground Testing, and Flight Testing Conference 2012
DOI: 10.2514/6.2012-3200
|View full text |Cite
|
Sign up to set email alerts
|

Time Resolved Filtered Rayleigh Scattering for Temperature and Density Measurements

Abstract: Early development of a spatio-temporally resolved filtered Rayleigh scattering (STR-FRS) instrument to measure temperature and density in compressible flows is discussed. This technique relies on new detector technology and FPGA data acquisition which promises many point, high repetition rate measurements. Results from a small cold jet are presented using similar technology as the full STRFRS technique, showing the robust fundamentals of the technique. Expected ratios of filtered-to-unfiltered Rayleigh scatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…In this paper, we developed a method called support vector spectrum approximation (SVSA) that uses machine learning to create efficient and accurate approximations of any existing spectral lineshape model in arbitrary flow regimes.The ability to produce approximations of existing lineshape models very efficiently is paramount for time-sensitive applications. In addition to our example of greatly speeding up a computational FRS study, we expect that SVSA will have application to real-time diagnostic techniques where efficiently calculating the lineshape from a continuous stream of data is necessary (Yeaton et al, 2012;Binietoglou et al, 2016). Additionally, we expect that SVSA will have application to problems outside of FRS and the RB spectra, for example, in approximating Raman spectra as part of CARS.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this paper, we developed a method called support vector spectrum approximation (SVSA) that uses machine learning to create efficient and accurate approximations of any existing spectral lineshape model in arbitrary flow regimes.The ability to produce approximations of existing lineshape models very efficiently is paramount for time-sensitive applications. In addition to our example of greatly speeding up a computational FRS study, we expect that SVSA will have application to real-time diagnostic techniques where efficiently calculating the lineshape from a continuous stream of data is necessary (Yeaton et al, 2012;Binietoglou et al, 2016). Additionally, we expect that SVSA will have application to problems outside of FRS and the RB spectra, for example, in approximating Raman spectra as part of CARS.…”
Section: Discussionmentioning
confidence: 97%
“…While typically quite accurate, such lineshape models are often computationally demanding. Thus, they are not ideal for situations where computational speed matters, for example, in optimization studies or real-time diagnostic techniques (Yeaton et al, 2012;Binietoglou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To get a density-dependent convolution spectrum, Yeaton et al [29] identified that the statistical expectation of the total number of Rayleigh scattered photons incident on the camera sensor can be written as Eq. ( 13) where P o is the incident laser power, n is the molecular number density, L x is the length of the measurement volume along the propagation direction, λ is the wavelength of the incident light, Ω is the light collection angle, ∆t is the time integration (camera exposure time), ϵ is the efficiency of the optical measurement system, h is the Planck constant, c is the speed of light, dσ dΩ is the differential scattering cross-section, and β is the angle between the laser polarization and the scattering direction.…”
Section: Convolution Modeling Of Rayleigh Scattering and Iodine Trans...mentioning
confidence: 99%
“…The solved stoichiometric equation can be seen in Eq. (29). Given the stoichiometric coefficients and the molecular weight of CO 2 = 44g/mol, H 2 O = 18g/mol, N 2 = 28g/mol, and O 2 = 32g/mol, the mole fractions of each product can be found.…”
Section: Jetcat Setup and Combustion Product Modelingmentioning
confidence: 99%
“…While stereoscopic PIV provides three-component-velocity measurement of both mean and turbulence quantities, it has some practical limitations, such as the need for a near-optimal distribution of seeding particles and difficulties for measuring scalar flow properties. Recently, the Virginia Tech team has begun to develop a robust application of the filtered Rayleigh scattering (FRS) technique for mean measurements of vector velocity, temperature and pressure Yeaton et al, 2012). The overall objective of the effort is to replace inlet distortion rakes made standard by the SAE S-16 Committee with this high-resolution optical method (ARP1420C, 2017).…”
Section: Seedless Velocimetry: Filtered Rayleigh Scatteringmentioning
confidence: 99%